Radar signals classification - Pieniężny, Andrzej; Kawalec, Adam (Видавництво Львівської політехніки, 2012)
The paper presents on the base of theoretical approach of time-frequency analysis and time-frequency representation optimizations, classification results of real radar signals. The results show, that applying class-dependent methodology it is possible to achieve acceptable classification level on the base of few intercepted pulses.
Keywords: Radar signal; time-frequency analysis; signals classification